Increased incidence of overweight and obesity among preschool Swedish children during the COVID-19 pandemic. (8th December 2022) - Fäldt, Anna; Nejat, Sahar; Edvinsson Sollander, Sofia; Durbeej, Natalie; Holmgren, Anton
Abstract: Background: The COVID-19 pandemic has had wide effects on child health globally. Increased prevalence of childhood obesity has been observed by a number of countries during the pandemic. The absence of a formal societal lockdown during the pandemic, made Sweden stand out compared to other countries. This study aims to examine changes in BMI among preschool children in Sweden before and during COVID-19 pandemic. Methods: Retrospective population-based cross-sectional study, with longitudinal follow-up for a portion of the children. The study included 25 049 children from three Swedish regions, with growth measures at 3- ( n  = 16 237), 4- ( n  = 14 437) and 5-years of age ( n  = 11 711). Care Need Index was used as a socioeconomic parameter at health centre level. Results: There was an increase in BMI in children aged three ( P  = 0.028) and four ( P <0.001) during the COVID-19 pandemic. Obesity in 3-year-old girls increased from 2.8% to 3.9%. Four-year-olds increased in obesity, and overweight (girls) and the prevalence of underweight decreased in boys. No change in BMI was observed in 5-year-olds. Children in areas of low socioeconomic status had higher risk of obesity. Conclusions: Overweight and obesity increased among 3- and 4-year-old children in Sweden, findings that were accentuated in children attending child health centres in areas with lower socioeconomic status. The COVID-19 pandemic is likely to have affected health behaviours negatively in Swedish preschool children. Our results expose the need for extended efforts directed to prevent childhood obesity, especially targeting lower socioeconomic areas.